Food safety policies and their effectiveness to prevent foodborne diseases in catering establishments: A systematic review and meta-analysis. (June 2022) - Levy, Noémie; Cravo Oliveira Hashiguchi, Tiago; Cecchini, Michele
Graphical abstract: Highlights: This study reviews the evidence on the impact of food safety policies to prevent foodborne diseases in catering services. Food safety interventions are associated with a microbial reduction of 28.6% (95% CI: −30.6% to −26.7%). Analyses by organism, sample origin, food establishment and collection time show consistent results with the main analysis. Sensitivity analyses confirm the overall strength of the results and the related policy recommendations. Abstract: Despite being largely preventable, foodborne diseases continue to be of major concern worldwide. Research has shown that interventions relying on food handling training programs and standard food safety practices have a direct impact on food handler's knowledge and attitudes. However, to date, evidence on the effectiveness of policies in reducing microbial count in food is sparse and inconclusive. This systematic review and meta-analysis aims to summarize the evidence on the potential of food safety policies in catering establishments as a means to prevent foodborne diseases. A search for relevant publications was conducted in PubMed, Scopus, CENTRAL, ProQuest, CINAHL and ERIC databases. Retrieved studies were summarised in terms of context, population, outcome, methodology, risk of bias and intervention type. Eight studies were included in the qualitative analysis and the meta-analysis. Food safety interventions were associated with a statistically significant microbial reduction of 28.6% (95% CI: −30.6% to −26.7%). Four subgroup analyses were conducted: by type of microorganism screened, by sample origin, by type of food establishment, and by sample collection time post-intervention. Microbial reductions were consistent across each of the subgroups. Findings suggest that policies such as programs based on the Hazard Analysis and Critical Control Points (HACCP) could be effective strategies to prevent foodborne diseases from occurring in foodservice establishments at the end of the food supply chain. However, the underlying evidence suffers from risk of bias and more randomized controlled trials and controlled before-and-after studies are needed in this field.